The Effect of Firm Sizes, Profitability, Dividend Policy, Asset Structure, Sales Growth and Free Cash Flow on Debt Policy - Ria Nurdani; Ika Yustina Rahmawati (Management Institute Faculty of Economics Universitas Andalas, 2020)
The study aims to examine the effect of company size, profitability, dividend policy, asset structure, company growth and free cash flow on debt policy. The object of this study uses manufacturing companies listed on the Indonesia Stock Exchange. The data used is secondary data in the form of annual financial statements for the 2015-2018 period. The collection technique used in this study was purposive sampling while the data analysis techniques used in this study were descriptive statistics, classic assumption tests, multiple regression analysis and hypothesis testing. The analysis show that the size of the company has a negative and not significant effect on debt policy, profitability has a negative and significant effect on debt policy. Dividend policy variables and asset structure has a negative and significant effect on debt policy. While sales growth and free cash flow has no effect on debt policy.